Purple Sweet Potato Drop Cookies Reception - Gita Garnapuspita; Ai Mahmudatusaadah; Yulia Rahmawati (Universitas Pendidikan Indonesia (UPI), 2023)
Purple sweet potato has a shelf life of only 15-20 days. Storing sweet potatoes for a very long time is prone to making the sweet potatoes sprout and experience changes in taste.Purple sweet potato flour is one of the simplest processed products from purple sweet potato.Purple sweet potato flour can be used in the innovation of making pastry products, namely cookies. The purpose of this study was to determine the processes involved in the development of cookies products and to determine the acceptability of the drop of purple sweet potato cookies. The method used in this research is the experimental method. Based on data processing, the results of the QDA oranoleptic test and the hedonic organoleptic test that had been carried out by 5 expert panelists on 4 trial products, namely DCUU 1, DCUU 2, DCUU 3 and DCUU 4. The organoleptic test results obtained the product with the best formulation, namely DCUU 4. Based on data processing and organoleptic test results (acceptability test) to 30 untrained panelists stated that the drop cookies product made from purple sweet potato was very positively received by consumers.